Business Development Strategy Analysis to Increase Visitors at Kampoeng Vietnam Tourism Attraction in Bandar Lampung - Robby Aji Saputra; Dora Rinova (Citakonsultindo, 2026)
Tourism destinations must continuously develop business strategies to remain competitive and attract visitors. Kampoeng Vietnam in Sumber Agung, Kemiling, Bandar Lampung, is a nature-based destination offering mountain views, green hills, sea scenery, cool air, and instagramable photo spots. However, it still faces challenges such as limited attraction variety, undeveloped cultural and special-interest tourism, poor road accessibility, and limited use of digital marketing. This study aims to analyze business development strategies for increasing visitors to Kampoeng Vietnam. Using a descriptive qualitative case study approach, data were collected through observation, interviews with the owner, staff, and visitors, documentation, and visitor data analysis. The analysis applied the 4A tourism concept, consisting of attraction, accessibility, amenities, and ancillary services, supported by SWOT analysis. The findings show that Kampoeng Vietnam has strong natural tourism potential, affordable entrance fees, adequate facilities, live music, and supporting services. Therefore, integrated strategies involving attraction diversification, digital marketing optimization, improved access, better signage, facility enhancement, and community collaboration are needed to increase visitor interest and support sustainable tourism development. These efforts can significantly strengthen competitiveness and encourage repeat tourist visits.